Chirality-controlled enantiopure crystal growth of a transition metal monosilicide by a floating zone method. (1st April 2022) - Kousaka, Yusuke; Iwasaki, Satoshi; Sayo, Taisei; Tanida, Hiroshi; Matsumura, Takeshi; Araki, Shingo; Akimitsu, Jun; Togawa, Yoshihiko
Abstract: We performed a crystal growth to obtain chirality-controlled enantiopure crystals using a laser-diode-heated floating zone (LDFZ) method with a composition-gradient feed rod. It has been argued that the crystal handedness of T Si ( T : transition metal) is fixed depending on T in the case of the ones grown by the conventional methods. We found that right-handed single crystals of CoSi and MnSi were grown from the composition-gradient feed rods that consist of FeSi–CoSi and FeSi–MnSi, respectively. The obtained CoSi and MnSi crystals inherit the chirality from the seed part of FeSi, which grows in a right-handed structure, and thus has the chirality opposite to that for the crystals in the literature. The LDFZ method with the feed rods with various combinations of T Si compounds enables flexible control of the chirality of T Si and will be useful for clarifying the interplay between crystalline chirality and chirality-induced physical responses.